Blood pressure characteristics and responses during resistance exercise - Apkarian, M. R. (Strength and Conditioning Journal, 2021)
Blood pressure changes acutely during resistance exercise. Continuous, beat-by-beat assessment provides detailed temporal resolution of blood pressure profiles, through techniques including intra-arterial catheterization, photoplethysmography, or applanation tonometry. However, noncontinuous measurements may be conducted before and after resistance exercise through auscultatory sphygmomanometry or oscillometry. Blood pressures tend to increase across repetitions within sets, influenced by load magnitude, repetitions and sets performed, muscle mass recruited, and rest periods; the highest pressures result from multi-joint, large muscle group exercises. Evaluation of such factors may facilitate better understanding of blood pressure responses to acute resistance exercise and influence program design considerations relative to anticipated hemodynamic changes.